Coming collapse of China - "Chang , Gordon G" (London, 2001)
Fully revised and updated edition covering China's new membership of the WTO and with a new introduction. 'Damning data and persuasive arguments that should set some Communist knees a-knocking.' Kirkus Reviews'A compelling account of the rot in China's institutions and the forces at work to end the Communist Party's monopoly on power.' James A. Dorn, Cato Institute, Washington D. C., Co-Editor of China's future: Constructive Partner or Emerging Threat? 'Quite simply the best book I know about China's future. Gordon Chang writes marvellously and knows China well. I hope everyone concerned with that country will pay careful consideration to what he sees ahead.' Arthur Waldron, Director of Asian Studies, American Enterprise Institute; Lauder Professor of International Relations, University of Pennsylvania.'A tour de force not to be missed.' Willy Wo-Lap, Senior China Analyst at CNN's Hong Kong office and author of The Era of Jiang Zemin.'When he warns that China's two centuries of troubles are still not over, we had better take notice.' Andrew J. Nathan, Professor of Political Science, Columbia University; Co-Editor, The Tiananmen Papers.
Keywords: China- Economic conditions